2022
DOI: 10.1161/circulationaha.121.057623
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptor NR1D1 Regulates Abdominal Aortic Aneurysm Development by Targeting the Mitochondrial Tricarboxylic Acid Cycle Enzyme Aconitase-2

Abstract: Background: Metabolic disorder increases the risk of abdominal aortic aneurysm (AAA). NRs (nuclear receptors) have been increasingly recognized as important regulators of cell metabolism. However, the role of NRs in AAA development remains largely unknown. Methods: We analyzed the expression profile of the NR superfamily in AAA tissues and identified NR1D1 (NR subfamily 1 group D member 1) as the most highly upregulated NR in AAA tissues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…In addition, with increasing age, chondrocyte proliferation decreased, and mitochondrial senescence and dysfunction emerged, thereby increasing ROS production and the levels of fatty acids, glucose, and inflammation mediators and, eventually, cartilage damage [ 46 ]. α-KG is an essential metabolite of the mitochondrial TCA cycle that can regulate mitochondrial metabolism, antioxidation, and anti-inflammation [ [14] , [15] , [16] , [17] ], and its serum levels gradually decrease with age [ 30 ]. Accordingly, in the present study, we first quantified α-KG content in cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, with increasing age, chondrocyte proliferation decreased, and mitochondrial senescence and dysfunction emerged, thereby increasing ROS production and the levels of fatty acids, glucose, and inflammation mediators and, eventually, cartilage damage [ 46 ]. α-KG is an essential metabolite of the mitochondrial TCA cycle that can regulate mitochondrial metabolism, antioxidation, and anti-inflammation [ [14] , [15] , [16] , [17] ], and its serum levels gradually decrease with age [ 30 ]. Accordingly, in the present study, we first quantified α-KG content in cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…The tricarboxylic acid (TCA) cycle, also known as citric acid or Krebs cycle, occurs in the mitochondria in eukaryotes and regulates mitochondrial function and oxidative stress [ [14] , [15] , [16] , [17] ]. α-ketoglutarate (α-KG) is a key intermediate metabolite in the TCA cycle, also known as 2-oxoglutarate [ 18 ], which contributes to a variety of metabolic processes, including the biogenesis of numerous amino acids, nucleotide, lipid, and carnitine biosynthesis, and as a cofactor in numerous dioxygenases [ [19] , [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%
“…3 In our study, we found that the ACO2 protein is predominantly located in the cytoplasm/mitochondria of smooth muscle cells, and that nuclear receptor NR1D1 regulates mitochondrial metabolism and energy balance by targeting its downstream Aco2 promoter. 1 These findings support a crucial role of the mitochondrial TCA cycle in the pathogenesis of AAA. Whether NR1D1 acts as an nTCA enzyme transcription modifier to regulate AAA or other cardiovascular diseases is also intriguing and worth further investigation in future studies.…”
Section: In Responsementioning
confidence: 54%
“…Categorical variables were expressed as numbers (percentage). Independent sample t -test or Mann-Whitney U test was used to compare variables between PH patients with controls, while Pearson’s Chi-Squared test or Fisher exact test to compare the categorical variables ( 15 ). PASPcal was adjusted for TAPSE, FAC, RAP, RAA, RV/LV, LVGLS and RVGLS by multiple linear regression, and Bland-Altman plot was used for agreement analysis.…”
Section: Methodsmentioning
confidence: 99%